Thin filament cardiomyopathies: A review of genetics, disease mechanisms, and emerging therapeutics - Keyt, Lucas K.; Duran, Jason M.; Bui, Quan M.; Chen, Chao; Miyamoto, Michael I.; Silva Enciso, Jorge; Tardiff, Jil C.; Adler, Eric D. (Frontiers in Cardiovascular Medicine, 2022)
Cardiac contraction occurs due to the cyclical interaction between sarcomeric thin and thick filament proteins within the cardiomyocyte. The thin filament consists of the proteins actin, tropomyosin, Troponin C, Troponin I and Troponin T. Mutations in these proteins can result in various forms of cardiomyopathy, including hypertrophic, restrictive, and dilated phenotypes and account for as many as 30% of all cases of inherited cardiomyopathy. There is significant evidence that thin filament mutations contribute to dysregulation of Ca2+ within the sarcomere and may have a distinct pathomechanism of disease from cardiomyopathy associated with thick filament mutations. A number of distinct clinical findings appear to be correlated with thin-filament mutations: greater degrees of restrictive cardiomyopathy and relatively less left ventricular (LV) hypertrophy and LV outflow tract obstruction than that seen with thick filament mutations, increased morbidity associated with heart failure, increased arrhythmia burden and potentially higher mortality. Most therapies that improve outcomes in heart failure blunt the neurohormonal pathways involved in cardiac remodeling, while most therapies for hypertrophic cardiomyopathy involve use of negative inotropes to reduce LV hypertrophy or septal reduction therapies to reduce LV outflow tract obstruction. None of these therapies directly address the underlying sarcomeric dysfunction associated with thin-filament mutations. With mounting evidence that thin filament cardiomyopathies occur through a distinct mechanism, there is need for therapies targeting the unique, underlying mechanisms tailored for each patient depending on a given mutation.